L1CAM expression in either metastatic brain lesion or peripheral blood is correlated with peripheral platelet count in patients with brain metastases from lung cancer - Wang, Jia-Wei; Wang, Hong-Liang; Liu, Qi; Hu, Ke; Yuan, Qing; Huang, Sheng-Kai; Wan, Jing-Hai (Frontiers in Oncology, 2022)
Background Systemic immune-inflammation states across the heterogeneous population of brain metastases from lung cancer are very important, especially in the context of complex brain-immune bidirectional communication. Previous studies from our team and others have shown that the L1 cell adhesion molecule (L1CAM) is deeply involved in the aggressive phenotype, immunosuppressive tumor microenvironment (TME), and metastasis during multiple malignancies, which may lead to an unfavorable outcome. However, little is known about the relationship between the L1CAM expression and the systemic immune-inflammation macroenvironment beyond the TME in brain metastases from lung cancer. Methods Two cohorts of patients with brain metastases from lung cancer admitted to the National Cancer Center, Cancer Hospital of Chinese Academy of Medical Sciences, were studied in the present research. The L1CAM expression in cranial metastatic lesions by immunohistochemistry was explored in patients treated with neurosurgical resection, whereas the L1CAM expression in peripheral blood by ELISA was tested in patients treated with non-surgical antitumor management. Furthermore, based on peripheral blood cell counts in the CBC test, six systemic immune-inflammation biomarkers [neutrophil count, lymphocyte count, platelet count, systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio] were calculated. Then, the relationship between the L1CAM expression and these systemic immune-inflammation biomarkers was analyzed. In addition, these systemic immune-inflammation biomarkers were also used to compare the systemic immune-inflammation states in two cohorts of patients with brain metastases from lung cancer. Results Positive L1CAM expressions in the metastatic brain lesions were accompanied with significantly increased peripheral platelet counts in patients treated with neurosurgical tumor resection (P < 0.05). Similarly, in patients treated with non-surgical antitumor management, L1CAM expressions in the peripheral blood were positively correlated with peripheral platelet counts (P < 0.05). In addition, patients prepared for neurosurgical tumor resection were presented with poorer systemic immune-inflammation states in comparison with the one with non-surgical antitumor management, which was characterized by a significant increase in peripheral neutrophil counts (P < 0.01), SII (P < 0.05), and NLR (P < 0.05) levels. Conclusion The L1CAM expression in either the metastatic brain lesion or peripheral blood is positively correlated with the peripheral platelet count in patients with brain metastases from lung cancer. In addition, brain metastases that are prepared for neurosurgical tumor resection show poor systemic immune-inflammation states.